The application of Google Classroom from Malaysian teachers’ perspective / Peter Ong and Dr. Md Jais Ismail - Ong, Peter; Ismail, Md Jais (Universiti Teknologi MARA, Kedah, 2024)
The aim of this study is to examine the perception of teachers on the use of Google Classroom in the teaching process in public secondary schools in Kuala Lumpur. This study aims to examine teachers' perceptions of using the Google Classroom in the teaching process in public secondary schools in Kuala Lumpur. A total of 75 teachers from Kuala Lumpur's public secondary schools were randomly selected as respondents and 10 were interviewed. The questionnaire consists of 15 questions prepared using the Google online form and sent to 10 secondary schools in Kuala Lumpur. In the questionnaire, 15 items of the Likert scale and 2 interview questions were adapted to determine the perception of secondary school teachers on using Google Classroom in the teaching process. The data are analyzed according to each questionnaire element to obtain the mean and standard deviation. The mean and standard deviation have shown the high level of secondary school teachers’ perception on using the Google Classroom in the teaching process. The results indicate teachers have the positive perception on using Google Classroom in the teaching process. Besides, they do agree on using Google Classroom in the teaching process.